2002
DOI: 10.1029/2001jd000915
|View full text |Cite
|
Sign up to set email alerts
|

Neutral air turbulence and temperatures in the vicinity of polar mesosphere summer echoes

Abstract: [1] A total of 8 sounding rocket flights with measurements of neutral air turbulence in the upper mesosphere have been performed in the past 10 years with simultaneous and nearly co-located radar measurements of polar mesosphere summer echoes (PMSE). These measurements took place close to the rocket ranges in northern Norway (Andøya Rocket Range, 69°N) and in northern Sweden (Esrange, 68°N). A detailed comparison demonstrates that there is no apparent correlation between PMSE and neutral air turbulence and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
140
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(159 citation statements)
references
References 36 publications
18
140
1
Order By: Relevance
“…Lübken found that significant turbulence during this period only occurred between 78 and 97 km, peaking around 90 km. Later rocket measurements confirmed these results [Lübken et al, 2002]. Figure 2 shows that this is in contrast to the predictions of 2-D models, which predict a much broader region of turbulence extending from 70 km to above 110 km.…”
Section: Tuning the Eddy Diffusion Profilecontrasting
confidence: 49%
“…Lübken found that significant turbulence during this period only occurred between 78 and 97 km, peaking around 90 km. Later rocket measurements confirmed these results [Lübken et al, 2002]. Figure 2 shows that this is in contrast to the predictions of 2-D models, which predict a much broader region of turbulence extending from 70 km to above 110 km.…”
Section: Tuning the Eddy Diffusion Profilecontrasting
confidence: 49%
“…However, numerical simulations showed that only vigorous turbulence revealing heating rates of ∼ 10 K h −1 is capable of producing temperature inversions (Liu et al, 2000). Such strong turbulence, however, has rarely been observed (see, e.g., Lübken, 1997;Lübken et al, 2002) in contrast to the temperature inversion layers, which are common phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these observations can only be conducted when the CONE sensor is in ram position during the downleg part of the rocket trajectory (whereas all the observations presented here were obtained on the upleg part of the rocket trajectory). As described in Lübken et al (2002), the CONE sensor identified turbulent activity at altitudes between 87.5 and 90.5 km and between 92.5 and 93.5 km on the downleg part of the trajectory. If we would assume that the turbulence is homogeneous over the distance between upleg and downleg of the rocket trajectory (horizontal distance ∼50 km), we could classify the spectrum shown in Fig.…”
Section: Observed Spectramentioning
confidence: 99%
“…Ulwick et al, 1988). However, in recent years two experimental facts provided strong evidence against some parts of this theory: first, in situ measurements of neutral air turbulence in PMSE showed that neutral air turbulence regularly existed only in the upper altitude range with PMSE (Lübken et al, 2002). Secondly, in situ measurements of plasma parameters of the PMSE environment like number densities of electrons, positive ions and charged particles showed that in the majority of cases the charge residing on the particles is significantly less than the free electron number density (Havnes et al, 2001;Blix et al, 2003) contrary to the predictions of the Cho et al (1992)-theory. Recently, Rapp and Lübken (2003) proposed a possible solution for these two dilemmas: they reconsidered the question of electron diffusion in the vicinity of charged aerosol particles and found that in principle each perturbation of the negatively (positively) charged aerosol number density should also be reflected in anticorrelated (correlated) perturbations of the electron number density, independently of the actual ratio between charged particle number density and electron number density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation